ANALYSIS OF THE IMPACT OF THE AFRICAN SWINER FEVER (ASF) VIRUS ON INCOME AND INTEREST IN PIG PRODUCTION IN NAGEKEO DISTRICT - Y. Sola, German (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the impact of the African Swine Fever (ASF) virus on household income and the interest of pig farmers in Nagekeo Regency. The research method used in this study is a qualitative one.The data analysis used qualitative descriptive analysis. Survey results show the increase in ASF is particularly concerning for pig farmers. The number of pig deaths per day ranges from 10 to 20 pigs.Losses experienced by pig farmers are estimated at around 10,000,000 rupiah per day per pig farmer. Pig farmers experiencing significant economic losses, uncertainty about the recovery of their businesses, difficulties in recovering capital, and the need for sufficient capital to start a business.Pig farmers generally have an interest in raising pigs, but their knowledge of ASF is limited, potentially increasing the risk of disease spread. Pig farmers have not been able to restart their livestock farming businesses because the virus outbreak has not been resolved. The conclusion of this study is that pig farming communities in Nagekeo Regency with around 5 pigs in the period before ASF generated a good income of up to 10,000,000 per year. Negative impacts on pig farmers who were partially affected and affected by ASF from 2020-2025 ASF disrupted the economy so that they could not meet basic needs and decreased the level of their business scale. Farmers have not resumed their businesses due to capital constraints and are still traumatized by the ASF outbreak they experienced. Keywords: African Swiner Fever (ASF);Pig farming; Income;interest